La tour Eiffel dans la poche. Informalité et pouvoir dans la construction de la métropole touristique - Sandrine Berroir; Caroline Bouloc; Nadine Cattan; Antoine Fleury; Jean-Baptiste Frétigny; Ulysse Lassaube (L'Espace Politique)
Formality and informality, Global North and Global South as well as globalization from above and globalization on below are enduring dichotomies informing greatly our representations of cities. This paper envisions the overcoming of such oppositions by focusing on the power dynamics engaged by informality in the very city centre of a so called Global North metropolis. The study of the spatial and social arrangements contracted between (in)formal stakeholders of several Parisian tourist attractions highlights the multiple ways in which the urban official order is infringed by the stakeholders of the informal economy on an everyday basis. Despite the strong apparatus of security, these stakeholders manage to assert themselves in the power relationships at stake in the public spaces and to build an alternative power geometry, allowing to grasp new forms of urban order at play. They turn out to be co-producers of the metropolis by reshaping tourist representations and practices as well as urban landscapes.